Supply & Demand of Rice in Malaysia: A System Dynamics Approach - Farah Hanim Abdul Rahim; Nurul Nazihah Hawari; Norhaslinda Zainal Abidin (International Journal of Supply Chain Management, 2017)
This paper illustrates the development of a supply and demand model of rice in Malaysia to gain better understand on the factors that affect the rice supply and demand towards the rice production system in Malaysia. It is known that the population of citizens in Malaysia relies heavily on the rice as its staple food for daily consumption. Currently, Malaysia has about 75% rice self-sufficiency level (SSL). The Malaysian government has set a target of 100% rice SSL in the production to meet the demand of the growing population. In this study, the qualitative approach of system dynamics is employed to analyze the effect of the price, land availability and technology on the rice production in Malaysia by using the causal loop and stock flow diagrams. The finding of this study will be helpful to assist the government in better understand the causes and effects of the factors related to improve the policies of the production of rice in Malaysia.